Metal oxide-catalyzed hydrothermal liquefaction of Malaysian oil palm biomass to bio-oil under supercritical condition - Yim, S.C. (Elsevier B.V., 2017)
Effect of metal oxide catalysts such as CaO, MgO, MnO, ZnO, NiO, SnO, CeO2, Al2O3 and La2O3 on supercritical hydrothermal liquefaction of empty fruit bunch (EFB) derived from oil palm residues to bio-oil were studied in terms of product yields and characteristics. EFB, water and 1.0 wt metal oxide were loaded into an Inconel batch reactor, heated to 390 °C to reach 25 MPa at reaction time of 1 h. Among the tested catalysts, four most active metal oxides with lower electronegativity such as CaO, MnO, La2O3 and CeO2 were selected, and gave maximum relative yield of bio-oil at about 1.40 times that without catalyst. Based on GC–MS and FT-IR analyses, the presence of phenol and its derivatives, ketone, other aromatic compounds and carboxylic acid in bio-oils obtained were confirmed. Thermogravimetric (TG) analysis of obtained bio-oils showed three stages of thermal degradation behaviour. Modified Reverchon-Sesti Osseo model provides good fit for the experimental yield of bio-oil formed with the four most active metal oxide catalysts. © 2016 Elsevier B.V.